From Recovery to Rebalancing : China’s Economy in 2021 - World Bank (Washington, DC: World Bank, 2021)
Following a collapse in the first quarter of 2020, economic activity in China has normalized faster than expected, aided by an effective pandemic-control strategy, strong policy support, and resilient exports. While swift, the recovery has been uneven, with domestic demand recovering more slowly than production and consumption more slowly than investment. Real GDP growth is projected to slow to 2 percent this year before accelerating to 7.9 percent in 2021, as consumer spending and business investment continue to catch up, along with improving corporate profits, labor market conditions, and incomes. The growth outlook is predicated on the assumption that well-targeted containment efforts supported by the gradual rollout of effective COVID-19 vaccines starting in early 2021 will continue to keep new infection rates low and prevent the resurgence of large-scale outbreaks. Economic rebalancing toward services, innovation and consumption driven growth has important spatial implications. This issue is at the heart of the exploratory analysis of the focus chapter in this report. While regional disparities in output, labor productivity, and income have narrowed since the mid-2000s, convergence was driven by a surge in investment in lagging regions. This has led to growing financial imbalances, mounting debt, and diminishing returns that constrained further investment-driven catch-up growth. Moreover, as China seeks to rebalance its economy from investment to a more innovation- and services-driven growth model, it will need to embrace the growth potential of its most developed and innovative metropolitan areas and city clusters, shifting the growth pole back to the coastal regions. Against this backdrop, policies to foster market integration and reduce spatial frictions in factor markets would enable a more efficient spatial allocation of labor and capital, harnessing the benefits of agglomeration and urbanization. Such a shift will inevitably create tensions with other policy objectives, notably the aim to reduce inequality. Therefore, it will need to be accompanied by fiscal policies to ensure a more equitable delivery of public services and investment in human capital to mitigate the very real consequences of resultant spatial disparities on people’s lives and opportunities.